Producing games : from business and budgets to creativity and design - Cohen, Dan S., ....-; Bustamante, Sergio A., ....-; Park, Tae Joon, ....- (Amsterdam ; Boston : Focal Press, 2010)
Master the secrets behind video game production - from concept to completion - with these comprehensive tips and tricks from two accomplished, working game producers. Discover how to lead a team, communicate effectively, budget, schedule, staff, and design quality next-generation games. Producing Games walks you through every stage of the production process with a focus on the part the producer plays at each phase.
Includes index.
Keywords: Games -- Management; Video games industry -- Management; Video games -- Design